Arrangement of The Stambul Baju Biru Song By The Tjong Young Gita Citra Alam Keroncong Community - Hunafa, Kinanthi Wedhatu; Rachman, Abdul (Jurnal Seni Musik, 2025)
The Keroncong Community of Tjong Young Gita Citra Alam represents a successful effort to preserve the cultural heritage of keroncong music through experimental arrangement innovations, without losing the traditional character of the keroncong stambul style. This study aims to identify and describe the harmonic arrangement of Stambul Baju Biru by Tjong Young Gita Citra Alam. Data collection techniques employed a qualitative methodology with a musicological approach, including non-participant observation, interviews, and document studies. The findings reveal that the arrangement of Stambul Baju Biru incorporates additional sections such as an intro, a coda, and a solo voorspél, with the harmonization expanded experientially. From these findings, it can be concluded that the harmonization of Stambul Baju Biru is dominated by variations of chromatic chords, inversions, and slash chords, which are seamlessly connected vertically and horizontally. This harmonic complexity supports the expressive range of the song and facilitates smooth chromatic transitions between its sections.